PEREMPUAN DALAM CITRA KETIDAKADILAN GENDER (Kajian Feminis dan Resepsi atas Kisah Yusuf dalam Serat Yusuf) - Muwafiqotul Isma; Hatim Gazali (MUWAZAH : jurnal kajian gender, 2016)
In Islam, men and women are equal before God (das sollen). However, stereotype, discrimination and violance against woman often happen everywhere. The position of women according to the Serat Yusuf as a literature that was born from the social construction and the storage author who is gender bias placed women unequally. This research that used philology theory, reception theory and feminism theory examined the picture of unequal gender in Yusuf-Zulaikha in Serat Yusuf. Based on Philology theory, it was found that Serat Yusuf who was written by Nalaputra is a sung text. It was written in 1935 that consist of 29 chapters (pupuh). While based on the reception theory, the study revealed that the reading of Nalaputra as the writer of the Serat Yusuf on Yusuf- Zulaikha story that consists in the holy Quran experienced the expansion and additional part, plot, character. In the analysis of the feminist theory, the study discovered forms of unequal position of women such as women are perceived as a passive, emotional, unable to control their desire, men servants and their faith are lower than men.